Efektivitas Metode Edukasi Audiovisual terhadap Self Management pada Pasien Hipertensi - Fernalia Fernalia; Busjra Busjra; Wati Jumaiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effectiveness of audiovisual education methods on self management in hypertensive patients. This study used a quasi-experimental design with a non-equivalent control group pre and post test design, with a total sample of 38 respondents consisting of an intervention group and a control group. Obtained a significant difference in the average self-management of the intervention group after the audiovisual education method was performed with (p = 0,000). There was no relationship between age (p = 0.71), sex (p = 0.955) and self-management in hypertensive patients. While self management will increase after the audiovisual education method is carried out and controlled by knowledge (p = 0.005). The conclusion of this study is the audiovisual education method can improve self management in hypertensive patients. Keywords: Audiovisual Education, Hypertension, Self Management